Daniel A. Jenks papers - Jenks, Daniel A., 1827-1869.
Diaries (1859-1860 and 1863-1865) with color illustrations documenting Jenks's experiences on the Overland Trail during his return to California across the Great Plains and Rocky Mountains via Salt Lake City, Utah, and a journey he took driving livestock from Yreka, California, to Idaho Territory. Jenks provides his impressions of Native Americans in Idaho Territory and of Mormon residents in Salt Lake City. Also includes two letters (1849) to his parents and clippings (1852-1864) primarily from California and Idaho Territory newspapers.
Pioneer, gold miner, and drover.
Collection material in English.
Keywords: Jenkins family -- Correspondence; Jenks family -- Correspondence; Cattle trails -- Northwestern States; Indians of North America -- Idaho Territory; Mormons -- Utah -- Salt Lake City; Overland journeys to the Pacific; Overland Trails; California -- Description and travel; California -- History -- 19th century; Great Plains -- Description and travel; Idaho Territory -- Description and travel; Idaho Territory -- History -- 19th century; Northwestern States -- Description and travel; West (U.S.) -- Description and travel; Rocky Mountains -- Description and travel; Salt Lake City (Utah) -- Description and travel; Utah -- Description and travel; Utah -- History -- 19th century; Yreka (Calif.) -- Description and travel; West (U.S.) -- History -- 19th century; Drovers; Gold miners; Pioneers